MANAJEMEN DAKWAH BERKELANJUTAN PADA MASYARAKAT PINGGIRAN KOTA PADANG OLEH IKADI - Piter, Alexy (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
This research aims to explain the IKADI sustainable da'wah management process in strengthening community in the suburbs of Padang. This research uses qualitative methods with a field research approach. Based on the research results, it was found that firstly, the process of planning sustainable da’wah development activities for the community living in the suburbs of Padang was based on the empirical experience of IKADI missionaries in the field. Second, the process of implementing the activities was carried out in the form of a majlis taklim, remaja masjid, wirid in accordance with the plan. Which has been determined: third, the evaluation process is carried out by requesting reports from missionary officers in the field, both verbal and written reports.